Pengaruh Pengungkapan Manajemen Risiko Terhadap Nilai Perusahaan Melalui Kinerja Keuangan Di Industri Perbankan Indonesia - Agung Supriyadi; Christina Tri Setyorini (Owner : Riset dan Jurnal Akuntansi, 2020)
Investors assess and demand banks to improve their risk management. Then, the profit earned by the bank is not yet known the effect of risk management on firm value. The aim of this study is to determine the effect of risk management disclosures on firm value with profitability as a mediating variable. The population used in this study are all banks listed on the Indonesia Stock Exchange (IDX) in the period of 2016 to 2018. This type of research is a correlational study consisting of thirty-six banks as research samples. Furthermore, the sampling method used in this study was purposive sampling. The results showed that the disclosure of risk management has a positive effect on profitability and firm value. Then, the risks and opportunities in this study can be managed well by the company so that it has a positive effect on increasing the company's profitability. The market implication assumes that risk management disclosures can be used as one of the relevant information to increase the value of the company. However, profitability in this study cannot mediate the relationship between risk management disclosure and firm value. The size of profitability produced in banks in Indonesia is not a determining factor in managing a company's risk management activities. So it can be concluded that risk management is disclosed solely because it fulfills corporate responsibilities and complies with government regulations.